(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the role of women in the family upbringing process, creating a healthy upbringing environment in the family, in the era of rapid development of modern technologies. It also analyzes the issues of effective implementation of the educational function of women, organization of cooperation between families and educational institutions, and upbringing based on national and universal values.